44. EVALUATION OF THE EFFECTIVENESS OF ELECTROACUPUNCTURE AND ACUPRESSURE COMBINED WITH “TAM TY” PILL IN TREATING SCIATIC NEVRE PAIN CAUSED BY LUMBAR SPINE DEGENERATION (Vietnam Journal of Community Medicine, 2025)
Objectives: 1. To evaluate the effectiveness of electroacupuncture and acupressure combined with “Tam Ty” pill in reducing pain and improving mobility in the treatment of sciatic nerve pain due to lumbar spine degeneration. 2. To assess some adverse effects of the treatment method.Subjects and Methods: A prospective, uncontrolled clinical intervention study with 38 patients treated using electroacupuncture and acupressure combined with Tam Ty pills.Results: After 20 days of treatment, the Visual Analog Scale (VAS) pain score decreased from 5,6 ± 0,5 points to 1,6 ± 0,9 (p < 0.05). The Oswestry Disability Index (ODI) score decreased from 67,8 ± 5,2% to 23,2 ± 9,4% (p < 0.05), and the Lasegue angle increased from 35,4 ± 5,0 degrees to 65,5 ± 7,9 (p < 0.05).Conclusion: Electroacupuncture and acupressure combined with Tam Ty pills are effective in improving VAS pain score, ODI index, and the Lasegue angle in patients with sciatica.
Keywords: “Tam ty” pill; electroacupuncture; acupressure; sciatic